Current grading of gall bladder cholecystitis and management guidelines: Is it sufficient?. (December 2020) - Elkbuli, Adel; Meneses, Evander; Kinslow, Kyle; Boneva, Dessy; McKenney, Mark
Highlights: These two cases highlight the limitations in current grading systems, particularly in the context of gallbladder size. We propose modifications to the PGS to include not only abnormal anatomy but instances of distorted gallbladder anatomy due to inflammation and/or the large to giant size in order to account for the increased risk of complications. Both distorted gallbladder anatomy and giant gallbladder size can make laparoscopic cholecystectomy a challenge, and thus warrant contribution to overall clinical grade. While the PGS, Tokyo Guidelines, and AAST grading scales are validated grading scales for acute cholecystitis, additional modifications can further characterize different types of acute cholecystitis to better guide patient management.